2010
DOI: 10.1007/s11668-010-9398-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cooling Holes to Decrease the Amount of Thermal Damage on a Plastic Gear Tooth

Abstract: A new method was developed to decrease the amount of thermal damage on the contact surface of a plastic gear tooth. The main aim of this method is to decrease the amount of thermal damage on the tooth surface by reducing the heat accumulated in the tooth under working conditions. For this reason, air-cooling holes on the plastic gear tooth were drilled in different locations, with the intention of lowering the tooth temperature by transferring the heat away from the tooth through these holes via convection. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Gears with the second configuration underwent very less damage in comparison to the other configurations operating under the same conditions. 52 In another study, it was found that there was a significant reduction in the gear tooth temperature when the hole was drilled in the vicinity of the pitch diameter and a direction perpendicular to the tooth axis. 51
Figure 8.Solid model of: (a) first type of configuration; (b) second type of configuration (Source: Duzcukoglu et al.
…”
Section: Modification Techniques Employed To the Tooth Of Polymer Gearsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gears with the second configuration underwent very less damage in comparison to the other configurations operating under the same conditions. 52 In another study, it was found that there was a significant reduction in the gear tooth temperature when the hole was drilled in the vicinity of the pitch diameter and a direction perpendicular to the tooth axis. 51
Figure 8.Solid model of: (a) first type of configuration; (b) second type of configuration (Source: Duzcukoglu et al.
…”
Section: Modification Techniques Employed To the Tooth Of Polymer Gearsmentioning
confidence: 97%
“…51
Figure 8.Solid model of: (a) first type of configuration; (b) second type of configuration (Source: Duzcukoglu et al. 52 ).
…”
Section: Modification Techniques Employed To the Tooth Of Polymer Gearsmentioning
confidence: 99%
“…The surface of loading tooth was inspected by H. Duzcukoglu et al [17] to determine the presence of transverse crack. It was found that the transverse cracked occurred due to thermal softening caused by accumulated heat.…”
Section: Microstructure Surface Condition Monitoringmentioning
confidence: 99%
“…The improved heat dissipation ability increased the gears life considerably. The introduction of cooling holes was reported by H. Duzcukoglu [17] in order to decrease thermal damage. Three design of gears were studied, first is unmodified, the second gear had a hole drilled at the pitch point of the gear tooth and the third design have holes at the pitch point and on the body of the tooth as seen in Fig.…”
Section: Thermal Damage and Temperature Detection Using Thermal Camermentioning
confidence: 99%
“…Test results indicated a decrease in tooth surface temperature that led to a reduced wear rate. Düzcükoğlu coworkers improved the load‐carrying capacity of plastic gear by drilling air‐cooling holes on the tooth of the gear. The use of cooling holes decreases the amount of thermal damage to plastic gear tooth.…”
Section: Introductionmentioning
confidence: 99%